27Al NMR MAS Spectral Studies Inferring the Initiation of Geopolymerization Reaction on Together Mechanochemical Grinding of Raw Materials. Issue 4 (5th December 2017) - Bhardwaj, Pooja; Gupta, Rainy; Mishra, Deepti; Mudgal, Manish; Amritphale, Sudhir Sitaram
Abstract : Chemical shifts and intensities of the 27 Al NMR signals provide structural information about the environment of Al nuclei in presence of an external magnetic field. This paper analyzes the structural information of the aluminum nuclei present in the precursor material after mechanochemical co‐grinding of the raw materials, namely fly ash, NaOH, and amorphous tricalcium phosphate [Ca3 (PO4 )2 ], with the help of 27 Al MAS NMR spectral studies. The results indicate transformation of the sixfold coordination Al ions with oxygen AlQ6 present in aluminosilicate material fly ash to fourfold AlQ4 and fivefold AlQ5 in the precursor material. The variation in chemical shift is between δ 64 and 65 ppm. This indicates that, in addition to direct bonding to the oxygen atom, the Al tetrahedron is also bonded to Si as [AlQ4(4Si)]. Thus, the mechanochemical co‐grinding of the raw materials initiates a solid‐state chemical reaction among them. The addition of water alone to this precursor material results in the formation of the geopolymeric material unlike the conventional geopolymeric system which requires the addition of a highly alkaline aqueous solution to fly ash. This study helps in the determination of the reaction mechanism during the mechanochemical transformation of raw materials into the geopolymeric product by a novel process. Abstract : 27 Al NMR MAS Spectral Studies confirms the diffusion of Al into the Si–O–Si covalent framework in the geopolymeric precursor obtained by novel process of mechanochemical grinding of raw materials.